The Orexin-A/OX1R System Induces Cell Death in Pancreatic Cancer Cells Resistant to Gemcitabine and Nab-Paclitaxel Treatment - Voisin, Thierry; Nicole, Pascal; Gratio, Valérie; Chassac, Anaïs; Mansour, Dounia; Rebours, Vinciane; Couvelard, Anne; Couvineau, Alain (Frontiers in Oncology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) represents the fourth cause of cancer-associated death in the West. This type of cancer has a very poor prognosis notably due to the development of chemoresistance when treatments including gemcitabine and Abraxane (Nab-paclitaxel) were prescribed. The identification of new treatment circumventing this chemoresistance represents a key challenge. Previous studies demonstrated that the activation of orexin receptor type 1 (OX1R), which was ectopically expressed in PDAC, by its natural ligand named orexin-A (OxA), led to anti-tumoral effect resulting in the activation of mitochondrial pro-apoptotic mechanism. Here, we demonstrated that OxA inhibited the pancreatic cancer cell (AsPC-1) growth and inhibited the tumor volume in preclinical models as effectively as gemcitabine and Nab-paclitaxel. Moreover, the combination therapy including OxA plus gemcitabine or OxA plus Nab-paclitaxel was additive on the inhibition of cancer cell growth and tumor development. More importantly, the treatment by OxA of chemoresistant tumors to gemcitabine or Nab-paclitaxel obtained by successive xenografts in mice revealed that OxA was able to induce a strong inhibition of tumor development, whereas no OxA resistance was identified in tumors. The OX1R/OxA system might be an innovative and powerful alternative treatment of chemoresistant PDAC.